Wade & Forsyth's administrative law - Forsyth, C. F.; Ghosh, Julian; Wade, William (Oxford University Press, 2023)
"Wade and Forsyth's Administrative Law has been a cornerstone text since publication of the first edition in 1961. It provides a comprehensive and perceptive account of the principles of judicial review and the administrative arrangements of the United Kingdom. For over sixty years, this text has been trusted by students and is extensively cited by courts throughout the common law world. The book's clarity of exposition makes it accessible to students approaching the subject for the first time, whilst its breadth of coverage and perceptive insight ensure its value to all interested in the field, academics and practitioners alike."-- Provided by publisher